Multidisciplinary or Monotherapy? Effects of Multidisciplinary Approach in Sotos Syndrome - Bingöl Rahime Hülya; Turna, Fatma; Gagachovska, Biljana; Kocabasoglu, Nese (Journal of Psychology and Psychotherapy Research, 2014)
Objectives: Paper presents impact of multidisciplinary approach in treatment of patients with Sotos Syndrome. Design: 36 months old female patient with Sotos syndrome was presented to us three years ago with an atypical development of communication and social interaction, inattentivity, hyperactivity and overall difficulty to manage her. She met diagnostic criteria for atipic childhood autism and specific training for autism was applied. At the age of five years and nine months Stanford Binett test was applied with a result of learning disability and the patient started receiving specific training. Results: Development was shown very quickly, she learned reading and writing, inattentivity and hyperactivity disappeared. Conclusions: Sotos syndrome is syndrome with multiple anomaly and common developmental and behavioral problems. Patients have a high risk of developing ADHD, temper tantrums and present autistic features. Academic difficulties and learning disabilities occur in most of them. Specific cognitive deficit may be present while levels of general intelligence stays unimpaired.